Overview of the Function of Traffic Signs and Markers in Bengkalis City to the Level of Understanding of the Community: a case study of urban roads in Bengkalis District - Arsyistawa Arsyistawa; Faisal Ananda (Nusantara Civil Engineering Journal, 2023)
Traffic signs are part of road equipment in the form of symbols, letters, numbers, sentences, or a combination of these. Even though traffic signs and road markings are placed at various points in Bengkalis City, there are still problems in understanding and the low level of public compliance with traffic signs and markings. The method used in reviewing the function of traffic signs and markings in the city of Bengkalis on the level of understanding and compliance of the community is using quantitative and qualitative research types and analyzed using IBM SPSS Statistics 27 and classifying using a decision tree. From the research results obtained 61.11% signs with good condition, 38.89% with damaged conditions. The condition of the markings resulted in 27.16% of the markers with good conditions and 72.84% with damaged conditions. The level of public understanding of the function of traffic signs and markings is 77% understanding.